Современное состояние теории и техники электродинамических устройств с нелинейными характеристиками поверхностного импеданса - Гавва, Д. С.; Крикун, Е. В.; Лучанинов, А. И. (ХНУРЕ, 2011)
HTS-devices possess nonlinear properties which result in appearance of undesirable nonlinear effects. In the article the modern state is considered in area of technique of microwave HTS-devices, methods of their analysis.
Keywords: ВТСП; электродинамические устройства; нелинейные эффекты; граничные условия; поверхностный импеданс